2016
DOI: 10.1083/jcb.2136oia121
|View full text |Cite
|
Sign up to set email alerts
|

Molecular functions of the transcription factors E2A and E2-2 in controlling germinal center B cell and plasma cell development

Abstract: 1201B cell immunity provides acute and long-term protection of the host against infections through the generation and secretion of high-affinity antibodies that recognize a shear unlimited number of pathogens. This enormous adaptive potential of B cells is brought about by V(D)J recombination of the immunoglobulin heavy chain (Igh) and light chain (Igk and Igl) genes in early B cell development, and by subsequent affinity maturation of the Ig heavy chain in late B cell differentiation (Victora and Nussenzweig,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 44 publications
(64 reference statements)
2
40
0
Order By: Relevance
“…3C). This defect was not surprising as E2A has been shown to be critical for both the growth of several Burkitt Lymphoma lines as well as a critical TF in GC B cells . Since the accumulation of mutations might be linked to cell division, it is possible that some or all of the SHM defects in the clone are explained by decreases in proliferation.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…3C). This defect was not surprising as E2A has been shown to be critical for both the growth of several Burkitt Lymphoma lines as well as a critical TF in GC B cells . Since the accumulation of mutations might be linked to cell division, it is possible that some or all of the SHM defects in the clone are explained by decreases in proliferation.…”
Section: Resultsmentioning
confidence: 97%
“…Here, we show that transcription factor binding at these DIVAC elements correlates with targeting of SHM in the context of an SHM reporter assay. Using a proteomics approach, we uncovered numerous factors that interact biochemically with DIVAC elements—with a number of them, including E2A, MEF2B, and members of the Ikaros family reported to be involved in B cell development or GC B cell function .…”
Section: Discussionmentioning
confidence: 99%
“…The observation of either loss-of-function mutations in Id3 or gain of function of E2A in Burkitt's lymphoma validates Id3's role as a tumor suppressor. Physiologically, E2A mediates germinal center B cell survival and function through critical genes, while the upregulation of Id proteins keeps their activity in check [63,117]. In the case of BL, the lack of E2A inhibition by mutated Id3 perpetrates a tonic BCR and PI3K signaling that drives GC B cellderived lymphomagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…S2). 23 A previous study showed that E2A binds to multiple regulatory elements across the human Igj gene, including E3ʹ. 23 A previous study showed that E2A binds to multiple regulatory elements across the human Igj gene, including E3ʹ.…”
Section: Yy1 Suppresses Igj Expression In Human B Lymphoma Cellsmentioning
confidence: 99%
“…2018 John Wiley & Sons Ltd, Immunology, 155, 491-498(encoded by the TCF4 gene) are essential for both GC Bcell and plasma cell development and that the levels of E2A remain high at both stages of B-cell development 23. …”
mentioning
confidence: 99%